Overexpression of CD97 in intestinal epithelial cells attenuates LPS-induced pro-inflammatory cytokine induction via stabilization of β-catenin early in life - Niklas Dressler; Steffi Mayer; Thomas Wiemers; Florentine Weise; Xiaoyan Feng; Gabriela Aust; Nicole Peukert; Martin Lacher; Jan Riedel (PLoS ONE, 2026)
Acute inflammatory conditions in the intestine of preterm infants are linked to increased susceptibility due to the immature degree of the gut’s epithelial barrier, microbiota, and pattern recognition receptors. Toll-like receptor 4 (TLR4) plays a pivotal role in recognizing lipopolysaccharides (LPS) from gram-negative bacteria, triggering pro-inflammatory cytokine responses (TNF-α, IL-1β, CXCL1) via nuclear factor kappa B (NF-κB) signaling. These processes are implicated in necrotizing enterocolitis (NEC), a severe gastrointestinal condition in premature infants. CD97, an adhesion G-protein coupled receptor (aGPCR), has emerged as a modulator of immune responses influencing inflammatory signaling pathways. CD97 expression is typically low in intestinal epithelial cells (IECs); however, protective effects of increased CD97 levels have been described in experimentally induced colitis. In this study, we examined the role of CD97 in modulating the inflammatory response in the immature gut, utilizing wild-type (WT) and transgenic CD97-overexpressing mice (TgCD97) with epithelial-specific expression in the intestinal epithelium. LPS was administered to IECs and organ segments isolated from the small intestine of mice of specific ages, modeling certain stages of human perinatal/postnatal gut development. CD97 overexpression attenuated LPS-induced TNF-α expression in IECs during early intestinal development while IECs from adult mice remained unaffected. This effect was attributed specifically to ileal tissue. Attenuation was mediated by β-catenin stabilization, leading to suppressed LPS/NF-κB signaling. Inhibition of β-catenin in TgCD97 IECs reversed the anti-inflammatory phenotype restoring pro-inflammatory gene expression. These findings suggest that CD97 overexpression modulates the inflammatory response in the developing gut by stabilizing β-catenin and interacting with the LPS/NF-κB axis. This effect was restricted to early developmental stages and ileal tissue, highlighting a previously unrecognized role of CD97 in age-dependent endotoxin tolerance. These findings identify a novel CD97-β-catenin-NF-κB regulatory axis in the immature small intestine and highlight its potential as a therapeutic target to protect the immature neonatal gut from inflammatory damage.